Impact of CYP3A5 Genotype on De-novo LCP Tacrolimus Dosing in Kidney Transplantation (Precision Medicine Communications, 2023)
The CYP3A5 gene encodes an enzyme called cytochrome P450 3A5, which is involved in the metabolism of many drugs, including tacrolimus. Tacrolimus is an immunosuppressive medication commonly used in kidney transplantation to prevent organ rejection. The CYP3A5 genotype can influence the metabolism and clearance of tacrolimus, leading to variations in the drug levels and response. LCP tac (an extended-release form of tacrolimus) has a recommended starting dose of 0.14 mg/kg/day in kidney transplants. Rao et al assessed the influence of CYP3A5 genotypes on perioperative LCP tac dosing and monitoring in adult kidney recipients receiving de-novo LCP tac. CYP3A5 genotype was measured, and 90-day pharmacokinetic and clinical were assessed. Patients were classified as CYP3A5 expressors (*1 homozygous or heterozygous) or nonexpressors (LOF *3/*6/*7 allele). They concluded that CYP3A5*1 expressors require higher doses of LCP tac to achieve therapeutic concentrations and are at higher risk of subtherapeutic trough concentrations, persisting for 30-day posttransplant. LCP tac dose changes in CYP3A5 expressors are more likely to be under-adjusted by providers. Pharmacogenet Genomics. 2023 Apr 1;33(3):59-65.  doi: 10.1097/FPC.0000000000000494.